Comparação entre registros de dados primários, Declarações de Nascidos Vivos e Sistema de Informações sobre Nascidos Vivos da Região de Saúde de Diamantina Minas Gerais - Daisy de Rezende Figueiredo Fernandes (2013)
The aim of this study was to compare the data obtained by interviews on maternal, obstetric and infant conditions births 2009 with those contained in the Birth Certificates and database of regional module Information System on Live Births the Diamantina Health Region. Initial comparisons were on the quantitative the Birth Certificates issued in hospitals and, or the Civil Registry and hospital and home births identified. The others were on the completeness and reliability of data from interviews with those of Birth Certificates and regional module Information System on Live Births (Article 1). The situation of maternal schooling and its association with the conditions of the births were also analyzed (Article 2). The Birth Certificates issued during the period were located, transcribed or copied, arranged in chronological order of occurrence of births and defined a representative sample by city. A data collection instrument was developed, the schedule of home visits for interviews was established and data collection occurred at home or Basic Health Units and hospitals, for some situations. The Regional Superintendent of Health Diamantina available the data contained in the regional module that were part of the study sample. Data were stored, analyzed and compared using Epi Info 6.04. The variables were analyzed from the frequency distribution, measures of central tendency and dispersion. To analyze the association used the Chi- square, Fisher Exact Test and Odds Ratio (OD). Were issued in the period 2.353 Birth Certificates which probably reflected all the births. Of the 728 Birth Certificates sample, filling in fields as unknown or blank were few (0.3 % to 1.3 % and 0.1 % to 5.5 %). In the comparative analysis of the data records and 694 interviews (95.3 %) were considered. In interviews with the agreement of the major inconsistencies the Births Certificates were marital status, education, number of stillbirth, number of prenatal consultations and race/color. Between Birth Certificates and data from regional module Information System on Live Birth were the usual occupation and residential address. Between interviews data from regional module Information System on Live Birth were marital status, education, usual occupation, home address, number of prenatal consultations and race/color. Analysis of association between maternal education and obstetric , maternal and infant conditions showed a statistically significant association between having attended incomplete primary education and be multiparous (OD = 3.00, p = < 0.001), having had vaginal delivery (OD = 2,29 , p = < 0.001 ) and outside the hospital (OD = 11.19, p = 0.006), did not meet the minimum schedule of prenatal visits (OD = 1.87, p < 0.001 ) and reside in rural (OD = 3.24, p = <0.001). Regarding Information System on Live Birth are undeniable the efforts to make this an Information System for Healthcare Excellence. You can say with all certainty that many of the challenges have been met. The issue of the Birth Certificates in hospital where births occur has become a routine and identification data registered in blank or wrongly regarded as practically nonexistent institutions and ignored. As the next challenge will remain the records and faithful transcriptions of the data for these forms and for regional, state and national modules of the system. The current Birth Certificates, the result of a continuous process of changes experienced over time with additions, replacements and modifications, as well as diversity professionals became authorized to issue it is concrete proof of this relentless pursuit. Gaps still exist, but the development of studies like this one presented here, which monitor the quality of the data generated in terms of coverage, completeness and reliability, bringing reliable information and that reflect a regional reality act as an important proposal for improvement.